Fostering The Use of English in The School Environment, A Case Study at A State High School in East Java - Taufiq, Wahyu; Tamara, Pasya; Sujarwo, Gita; Nabhila, Calista; Firdaus, Rafli (Universitas Muhammadiyah Sidoarjo, 2024)
At the Senior High School level, English language competence becomes increasingly vital, particularly in the face of globalization issues. English in school is not only a classroom subject; it is also a means of communication skill. These two factors are critical for developing students' character and preparing them for either further education or entry into the highly competitive workforce. This study was conducted at a state high school in East Java, aiming to study the role of the school in the use of English in the school environment. It was found that the environment, the curriculum, and the roles of teachers as well as the students are interrelated in supporting the use of English in the school environment. It is intended that these systems will reinforce one another, promoting harmony in the classroom and the teaching and learning process.